Sustainability of Malay traditional craft and craftmanship as cultural heritage in Kuala Kangsar, Perak, Malaysia - Kamaruddin, Zumahiran; Abdul Latip, Nurul Syala; Mansor, Mazlina; Salleh, Nurul Hamiruddin; ., Lukmanul Hakim (Kulliyyah of Architecture and Environmental Design, IIUM, 2013)

(untitled)
This paper discusses the traditional craftsmanship that have been sustained in the making of traditional arts and crafts by local Malay craftsmen from the various places in the royal town of Kuala Kangsar, located in the state of Perak, Peninsular Malaysia. Series of interviews with the craftsmen and field observation were conducted and found that the Malay craftsmen’s drive for preservation of traditional crafts and craftsmanship had paved the way for sustainability of the Malay cultural heritage in the region through continuity of craft industries with local and fresh inspiration. Cultural themes with visual aesthetic of local motifs are depicted on the pottery, embroidery, metal ware and woodwork craftsmanship which make up the essential part of the heritage. Creative tradition can be seen on these crafts through their craftsmanship style and design, materials and texture, the embellishment technique and construction. Examination on the traditional arts production by the craftsmen exemplifies their distinctive craftsmanship that was sustained as regional identity. It was found that the industry of pottery is the most profound works that dominate the local art and craft especially in the area known as Sayong. The pottery produced by them are inspired and derived from old traditional techniques and aesthetics which signify their strong preferences to maintain and preserve the art tradition from this region. Apparently, the physical and practical nomenclatures of the local crafts extracted from the past traditions are still intact that exemplifies their distinctive attributes and meanings as cultural heritage for Kuala Kangsar. The challenge for the present Malay craftsmen is to continue encouraging and sustaining their interests in the art and craft production while attempting to maintain its perception of authenticity and uniqueness among local residents and visitors to the region. There is a potentiality for further investigation on the tangible and intangible authenticity and technical uniqueness of the art and crafts through scientific documentation and experimental study. This is significant effort to ensure the sustainable development of the traditional arts and crafts in harmony and unity with local environment and its community.